ChemInform Abstract: Structural Reorganization of Allyl Isothiocyanate into Pyrrole Ring under Superbase: A Straightforward Access to NH‐2‐(Alkylsulfanyl)‐1H‐pyrroles and N‐Alkyl‐2‐(alkylsulfanyl)‐1H‐pyrroles. Issue 17 (4th April 2013) - Nedolya, Nina A.; Brandsma, Lambert; Trofimov, Boris A.
Abstract In the presence of water, the method leads to formation of pyrroles (III).